Implementasi Kurikulum Merdeka dalam Mencegah Learning Loss - Prasetyo, Gunawan Langgeng; Nurdiyana, Nurdiyana; Nurhemah, Neng (Universitas Pamulang, 2023)
The independent curriculum plan is said to be a program aimed at overcoming learning loss. This study focuses on examining the extent to which the implementation of the independent learning curriculum prevents loss of knowledge and skills (learning loss) at SMPN 12 Kota Tangerang Selatan, including challenges for teachers and students to the inhibiting factors in its implementation. This exploratory strategy uses qualitative descriptive with the subject of discussion from the Principal of SMPN 12 Kota Tangerang Selatan, deputy head of curriculum and representatives of teachers from each grade level with data analysis techniques using data reduction, categorization, synthesis and drawing conclusions. The results of this study show that the implementation of the independent curriculum in preventing learning loss, identified the problem of learning loss, the stages of implementing the independent curriculum in preventing learning loss include the planning stage, the implementation stage to the evaluation stage and studies regarding prevention of learning loss as well as a description of the challenges of implementing the curriculum. for teachers and students on the implementation of the Independent Curriculum in preventing loss of knowledge (learning loss).